2007
DOI: 10.1097/01.tp.0000267647.03550.22
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Glucose Metabolism Under Calcineurin Inhibitors in the First Year After Renal Transplantation in Nonobese Patients

Abstract: This study shows the need to perform an oral GTT at 60 days and at the end of the first year of renal transplantation to adequately diagnose impaired glucose metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 23 publications
(24 reference statements)
4
16
1
3
Order By: Relevance
“…In addition, these abnormalities, along with a more common diagnosis of IFG, were already detected at 3 mo, persisting during the first posttransplantation year (Table 2), and may have contributed to the higher rate of posttransplantation cardiovascular events in this group (Table 1). A similar observation was reported by Cosio et al (13), who showed that recipients with NODAT or IFG at 1 yr exhibited higher fasting glucose levels from the first month after transplantation; therefore, these findings suggest that an OGTT may be especially indicated in recipients who have hypertriglyceridemia and/or IFG by the end of the third month after transplantation (10).…”
Section: Discussionsupporting
confidence: 71%
“…In addition, these abnormalities, along with a more common diagnosis of IFG, were already detected at 3 mo, persisting during the first posttransplantation year (Table 2), and may have contributed to the higher rate of posttransplantation cardiovascular events in this group (Table 1). A similar observation was reported by Cosio et al (13), who showed that recipients with NODAT or IFG at 1 yr exhibited higher fasting glucose levels from the first month after transplantation; therefore, these findings suggest that an OGTT may be especially indicated in recipients who have hypertriglyceridemia and/or IFG by the end of the third month after transplantation (10).…”
Section: Discussionsupporting
confidence: 71%
“…As a result, we labelled as diabetic even those patients who had a FPG ≥ 7.0 mmol/l but did not require pharmacological therapy for diabetes, unlike other studies. Furthermore, the mean age of recipients in this study (48 years) was higher than that reported in other studies (means ranging from 39 to 46.5), as was the BMI (mean 26.2 in this study compared to 23.5 to 25.6 in others) . Higher age and BMI may account for the higher incidence of NODAT in this study.…”
Section: Discussioncontrasting
confidence: 69%
“…The proportion of patients who developed NODM during standard-dose treatment was comparable with the Tac arm of a recent 6-month study which used a similar definition for NODM [28]. It has been reported that patients with high trough levels of Tac early after transplantation are prone to develop glycemic disorders and that the diabetogenic effect of Tac can be ameliorated by reducing the dose of Tac [3335]. …”
Section: Discussionmentioning
confidence: 76%